Tax revenue determinants: A systematic analysis of tax regulation understanding and service quality - Wijaya, Suparna; Sajjad, Muhammad; Mufid, Irsyad; Karo Karo, Julio Riones; Alfarizi, Muhammad Saddam; Fayaadh, Muhammad (PT Wim Solusi Prima, 2025)
Taxation represents a critical revenue source for nations worldwide, including Indonesia, reflecting direct societal contributions to national development. This study explores the impact of taxpayer understanding of regulations and tax service quality on compliance levels and their subsequent effect on tax revenue. Using a systematic literature review methodology, we analysed 30 articles from indexed sources including Google Scholar, Sinta, and Science Direct. Our findings reveal significant positive relationships between understanding of tax regulations, service quality, and tax revenue generation. Theoretical foundations of these relationships are examined through the lens of compliance theory, procedural justice theory, and the slippery slope framework. The study further identifies those investments in information technology, particularly machine learning analytics and digital transformation initiatives, offer promising solutions to enhance tax revenue predictions and address administrative challenges. Our analysis concludes that strengthening taxpayers' regulatory comprehension and improving service quality are not merely beneficial for increasing compliance but are essential for optimizing tax revenues to support sustainable and inclusive economic development. The study contributes to the tax policy literature by providing empirically-supported strategies for enhancing tax administration effectiveness in developing economies.